Active Distribution Grid Power Flow Analysis using Asymmetrical Hybrid Technique - Paramet Wirasanti; Egon Ortjohann (Institute of Advanced Engineering and Science, 2017)
A conventional distribution power flow analysis has to be improved regards the changes in distribution network. One of the changes is a grid operation because a new grid concept, e.g. micro-grid and aggregation, is aimed to be operated based on area itself. Consequently, each area can be actively operated in either grid connected mode or islanding mode. Hence, this paper proposes an asymmetrical power flow analysis using hybrid technique to support this flexible mode change. The hybrid technique offers an opportunity to analyze power flow in a decoupling way. This means that the power flow analysis can be performed separately in each grid area. Regards the distributed generation, this paper also introduces a model based on inverter-based operation, i.e. grid forming, grid supporting and grid parallel. The proposed asymmetrical hybrid load flow method is examined in three case studies, i.e. a verification study with the DIgSILENT PowerFactory, a demonstration of decoupling analysis approach and a performance study with the Newton-Raphson method.